Reliability of Electromagnetic Tracking of Scapular Orientation and Position in Healthy Sendentary Individuals - Biazotto, Camila Choqueta; Camarini, Paula Maria Ferreira; Tucci, Helga Tatiana; McQuade, Kevin James; Oliveira, Anamaria Siriani de (Revista brasileira de cineantropometria & desempenho humano, 2014)
Electromagnetic systems for motion analysis are claimed as a precise technique for tracking position and orientation of human body segments. To date, reliability electromagnetic tracking was described only for the dynamic assessment of the scapula motion, and no reliability studies on its resting posture or positioning were found. The aim of this study was to analyze intra- and inter-session reliabilities and absolute errors of the scapular orientation and position at habitual resting posture in healthy individuals. Twenty-two shoulder symptom-free individuals non participants in professional or recreational sports activities involving upper extremities were volunteers in this study. The equipment used was 3SPACE Liberty system (Polhemus Inc.). The same examiner collected the kinematic data from subjects in two different sessions, with an interval from seven to ten days. Intraclass Correlation Coefficient (ICC2,1 and ICC2, k) and Standard Error of Measurement (SEM) were calculated. Inter-session reliability ranged from good to excellent (ICC from 0.66 to 0.96) and intra-session reliability was excellent (ICC ≥ 0.97). SEM values found for linear distances were smaller than 0.02 cm and scapular rotations ranged from 0.72° to 5.48°. Results of this study demonstrated that electromagnetic data acquisition of scapula habitual posture is a reliable tool for defining scapular position and orientation in sedentary shoulder symptom-free individuals.